Sugarcane Variety Census: Florida 2002: SS AGR 265/SC080, 8/2007 - Glaz, B.; Vonderwell, J.; Gilbert, Robert A. (EDIS, 2007)
Part of the Florida Sugarcane Handbook, published by the UF Agronomy Department, June - October 2007.